2007
DOI: 10.1051/0004-6361:20066633
|View full text |Cite
|
Sign up to set email alerts
|

A critical test of empirical mass loss formulas applied to individual giants and supergiants

Abstract: To test our new, improved Reimers-type mass-loss relation, given by Schröder & Cuntz in 2005 (ApJ, 630, L73), we take a look at the best studied galactic giants and supergiants -particularly those with spatially resolved circumstellar shells and winds, obtained directly or by means of a companion acting as a probing light source. Together with well-known physical parameters, the selected stars provide the most powerful and critical observational venues for assessing the validity of parameterized mass-loss rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 29 publications
3
59
1
Order By: Relevance
“…This new formula has been tested using well-studied nearby stars with measured mass loss rates, reproducing them within the error bars (Schröder & Cuntz 2007). For these reasons, we used the SC05 mass loss rate formulation, instead of the R75 one.…”
Section: Mass Lossmentioning
confidence: 99%
“…This new formula has been tested using well-studied nearby stars with measured mass loss rates, reproducing them within the error bars (Schröder & Cuntz 2007). For these reasons, we used the SC05 mass loss rate formulation, instead of the R75 one.…”
Section: Mass Lossmentioning
confidence: 99%
“…The numerical factor 8 × 10 −14 was adjusted by Schröder & Cuntz [69] to provide an optimum fit to HB stars in two GCs, namely M5 (NGC 5904) and NGC 5927. Then, assuming SC = 1, Schröder & Cuntz [70] have shown that, unlike with the Reimers formula, one is able to obtain good agreement, within the error bars, with the empirical data for well-studied red giants and supergiants. Very recently, a predictive theoretical model for the mass-loss rates of cool stars has been proposed by Cranmer & Saar [28] which seems to provide an even better fit to the empirical data [see also 1].…”
Section: -P6mentioning
confidence: 88%
“…The treatment of the stellar mass loss rate as function of the governing stellar parameters has successfully been tested on globular clusters as well as for a set of well studied stars (Schröder & Cuntz 2007). Thus, the attained models of stellar evolution are expected to provide an accurate description of the time-dependent behavior of stellar luminosity (see Fig.…”
Section: Methodsmentioning
confidence: 99%